2020
DOI: 10.36660/abc.20190016
|View full text |Cite|
|
Sign up to set email alerts
|

Alterações Cardiovasculares em Pacientes Portadores de Lipodistrofia Familiar

Abstract: Romando et al. Alterações cardíacas na lipodistrofia familiarArq Bras Cardiol. 2020; 114(2):305-312

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Speculation exists that disrupted glucose metabolism associated with the condition may activate pro-hypertrophy genes, potentially explaining this correlation. Furthermore, it’s crucial to consider the involvement of laminopathies and the neuromuscular presentation in the intricate interplay between familial lipodystrophy and its cardiac manifestations ( 7 , 8 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speculation exists that disrupted glucose metabolism associated with the condition may activate pro-hypertrophy genes, potentially explaining this correlation. Furthermore, it’s crucial to consider the involvement of laminopathies and the neuromuscular presentation in the intricate interplay between familial lipodystrophy and its cardiac manifestations ( 7 , 8 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of sufficient AT leads to the accumulation of lipids in ectopic tissues and organs such as muscle, liver, pancreas, and epicardial tissue, contributing to insulin resistance and associated c o m p l i c a t i o n s , i n c l u d i n g d i a b e t e s m e l l i t u s ( D M ) , hypertriglyceridemia, polycystic ovary syndrome (PCOS), pancreatitis, metabolic fatty liver disease (MAFLD), and cardiovascular disease (CVD) (2,(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Nosso estudo também reassegurou que esses pacientes apresentam níveis mais altos de pressão arterial, como demonstrado em outras coortes. 13 Isso poderia ser um fator de confusão, como um gatilho para a hipertrofia miocárdica. Para superar essa limitação, realizamos uma análise univariada e multivariada para analisar os níveis de PAS como um potencial fator de confusão na relação entre LP e parâmetros ecocardiográficos.…”
Section: Discussionunclassified
“…Our study also reassured that these patients have higher arterial pressure levels, as demonstrated in other cohorts. 13 This could be a confounder as a trigger to myocardium hypertrophy. To overcome this limitation, we performed univariate and multivariate analysis to account for SBP levels as a potential confounder in the relationship between PL and echocardiographic parameters.…”
Section: Discussionmentioning
confidence: 99%